Factors Influencing Accounting Conservatism in Indonesian Transport Sector: Faktor-Faktor yang Mempengaruhi Konservatisme Akuntansi di Sektor Transportasi Indonesia - Jannah, Miftakhul; Rahayu, Duwi (Indonesian Journal of Law and Economics Review, 2024)
This research examines the impact of growth opportunity, debt covenants, capital intensity, and litigation risk on accounting conservatism in transportation companies listed on the Indonesian Stock Exchange from 2019 to 2021. Using multiple linear regression analysis on data from 34 companies, the study finds that growth opportunity, capital intensity, and litigation risk significantly affect accounting conservatism, whereas debt covenants do not. These findings suggest that companies adjust their conservatism levels based on growth prospects, capital intensity, and litigation risk to attract investors and manage political and tax costs. Future research should consider other sectors, additional variables, and longer periods to identify broader trends. Highlight: Growth opportunity, capital intensity, and litigation risk impact accounting conservatism. Multiple linear regression analysis on 34 transportation companies (2019-2021). Future research: other sectors, more variables, longer periods. Keyword: Accounting Conservatism, Growth Opportunity, Debt Covenants, Capital Intensity, Litigation Risk